P300‐mediated modulations in self–other processing under psychedelic psilocybin are related to connectedness and changed meaning: A window into the self–other overlap. Issue 17 (21st August 2020) - Smigielski, Lukasz; Kometer, Michael; Scheidegger, Milan; Stress, Cornelia; Preller, Katrin H.; Koenig, Thomas; Vollenweider, Franz X.
Abstract: The concept of self and self‐referential processing has a growing explanatory value in psychiatry and neuroscience, referring to the cognitive organization and perceptual differentiation of self‐stimuli in health and disease. Conditions in which selfhood loses its natural coherence offer a unique opportunity for elucidating the mechanisms underlying self‐disturbances. We assessed the psychoactive effects of psilocybin (230 μg/kg p.o.), a preferential 5‐HT1A/2A agonist known to induce shifts in self‐perception. Our placebo‐controlled, double‐blind, within‐subject crossover experiment ( n = 17) implemented a verbal self‐monitoring task involving vocalizations and participant identification of real‐time auditory source‐ (self/other) and pitch‐modulating feedback. Subjective experience and task performance were analyzed, with time‐point‐by‐time‐point assumption‐free multivariate randomization statistics applied to the spatiotemporal dynamics of event‐related potentials. Psilocybin‐modulated self‐experience, interacted with source to affect task accuracy, and altered the late phase of self‐stimuli encoding by abolishing the distinctiveness of self‐ and other‐related electric field configurations during the P300 timeframe. This last effect was driven by current source density changes within the supragenual anterior cingulate and right insular cortex. The extent of the P300 effect was associated with the intensity of psilocybin‐induced feelings of unity and changed meaning of percepts. Modulations of late encoding and their underlying neural generators in self‐referential processing networks via 5‐HT signaling may be key for understanding self‐disorders. This mechanism may reflect a neural instantiation of altered self–other and relational meaning processing in a stimulus‐locked time domain. The study elucidates the neuropharmacological foundation of subjectivity, with implications for therapy, underscoring the concept of connectedness. Abstract : Self‐referential processing pertains to the cognitive organization and perceptual differentiation of self‐stimuli, and its experimental perturbation offers a unique opportunity for elucidating the underlying mechanisms. We assessed the psychoactive effects of the potent preferential 5‐HT1A/2A agonist psilocybin during a verbal self‐monitoring task with assumption‐free multivariate randomization statistics applied to brain event‐related potentials. Treatment with psilocybin modulated self‐experience, interacted with self/other stimuli for task accuracy, and altered the electric field configurations during the P300 timeframe.